Profile, types, duration and severity of muscular dystrophy: a clinical study at a tertiary care hospital - P., Viswajyothi; M. V., Rambabu (International Journal of Advances in Medicine, 2018)
Background: The cause of muscular dystrophies is genetic. It is a disorder of muscular system. The classification of the muscular dystrophies is based on the signs and symptoms. Present study was done to evaluate the profile, types, duration and severity of muscular dystrophy at a tertiary care hospital. Methods: A hospital based cross sectional study was carried out at department of General Medicine, Malla Reddy Institute of Medical Sciences, Hyderabad from October 2015 to December 2017. During the study period, it was possible to study the 20 cases of muscular dystrophy. Results: Muscular dystrophy was more common in males. Maximum cases were of Duchenne type of muscular dystrophy. Majority of the patients presented at 5-10 years of age. Muscular dystrophy was seen in early childhood. Out of 10 patients of Duchenne muscular dystrophy five patients were of grade I. There was no correlation between the duration of the disease and the severity of the disability. All patients had lower limb proximal weakness. Pathological Q wave (width > 30 ms) and Pathological Q wave (depth >more than 25% of the QRS amplitude) were present in 35% of the cases. All patients had rhythm NSR and QRS +60 to +75. Conduction abnormality was present in 5% of the cases. In half of the patients, serum creatinine kinase levels are moderately elevated. Conclusions: Muscular dystrophies are a common disorder of the childhood. Detailed studies will help to focus more light on this condition to improve outcome in future patients.